2018
DOI: 10.1097/md.0000000000013505
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of C-reactive protein to albumin ratio in patients with lung cancer

Abstract: Background:To perform a meta-analysis of retrospective studies exploring the association of C-reactive protein to albumin (CAR) with overall survival (OS) in patients with lung cancer.Methods:Relevant studies were enrolled by searching databases of PubMed, Cochrane Library, Web of Science, and Embase were searched until July 16, 2017. We combined the hazard ratios (HRs) and 95% confidence intervals (CIs) to assess the correlation between CAR and OS in patients with lung cancerResults:Four studies involving 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…Our findings suggest that both host factors and tumor factors are important. Some previous studies have already shown that host factors, such as clinically measurable inflammatory biomarkers, are associated with poor survival in lung cancer . In addition to these inflammatory biomarkers for NSCLC patients undergoing ICI treatment, we demonstrated that the tumor factor TB was a useful poor prognostic factor.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our findings suggest that both host factors and tumor factors are important. Some previous studies have already shown that host factors, such as clinically measurable inflammatory biomarkers, are associated with poor survival in lung cancer . In addition to these inflammatory biomarkers for NSCLC patients undergoing ICI treatment, we demonstrated that the tumor factor TB was a useful poor prognostic factor.…”
Section: Discussionsupporting
confidence: 56%
“…The following variables were collected from patient electronic medical records: age, sex, Eastern Cooperative Oncology Group performance status (ECOG PS), smoking status, histology, stage, PD‐L1 expression, treatment line, type of ICI, clinically measurable inflammatory or nutritional biomarkers (such as neutrophil count, lymphocyte count, neutrophil to lymphocyte ratio [NLR], serum LDH, C‐reactive protein [CRP], albumin, and Glasgow prognostic score [GPS]), and TB. The GPS is a prognostic score that includes serum albumin and CRP levels . NLR cutoffs were determined based on a previously published study …”
Section: Methodsmentioning
confidence: 99%
“…CAR was shown to have a prognostic value in lung cancer with significant correlation to overall survival. 10 In a recent retrospective study on 160 patients with RA and 159 healthy controls, CAR was found to be higher than controls and positively correlated with DAS28-ESR. Therefore, CAR was proposed to be a novel inflammatory marker for monitoring disease activity in RA.…”
mentioning
confidence: 94%
“…The following relevant clinical and serological data were collected for each enrolled patient at the time of diagnosis before any treatment: The data included age; gender, family history, body mass index (BMI), tumor size, clinical treatment, Tumor Node Metastasis stage (TNM stage) (Edge et al 2010), white blood cell (WBC), neutrophils (N), lymphocyte (L), platelet (PLT), hepatitis B surface antigen (HbsAg), hepatitis B surface antibody (HBsAb), hepatitis B envelope antigen (HBeAg), hepatitis B envelope antibody(HBeAb), hepatitis B core antibody (HBcAb), hepatitis B core antigen (HBcAb), albumin (ALB), alkaline phosphatase (ALP), apolipoprotein AI (APOA), apolipoprotein B (APOB), C-reactive protein (CRP), lactic dehydrogenase (LDH), glutamyl transpeptidase (GGT), total bilirubin (TBIL), and direct bilirubin (DBIL). NLR was the ratio of neutrophil to lymphocyte ratio (Diem et al 2017); PLR was the ratio of platelet to lymphocyte (Diem et al 2017); SLR was the ratio of AST to ALT (Lee et al 2017); ABR was the ratio of APOA to APOB (Chang et al 2007); CAR was the ratio of C-reactive protein to albumin ratio (Deng et al 2018); prognostic index (PI): score 0 for CRP 10 mg/L or less and white cell count 11 × 10 9 /L or less, patients with only one of these abnormalities were allocated a score of 1, and if both of them were elevated were allocated a score of 2(Kasymjanova et al 2010); the prognostic nutritional index (PNI) was calculated according to the following formula: Alb (g/L) + 5 × lymphocyte count × 10 9 /L: score 0 for PNI > 45; score 1 if patients with PNI ≤ 45 (He et al 2018); Glasgow prognostic score (GPS) was classi ed as follows: patients with serum CRP > 10 mg/L and albumin < 35 g/L were classi ed as GPS 2; patients with CRP > 10 mg/L or albumin < 35 g/L were classi ed as GPS 1; patients with serum CRP ≤ 10 mg/mL and albumin > 35 g/L were classi ed as GPS 0 (Shiba et al 2017).…”
Section: Patient Selection and Data Collectionmentioning
confidence: 99%